Architectural decoration of the eastern frontier - Михаил Базилевич; Алина Иванова (Проект Байкал)
The article presents the results of the study conducted by the authors with the support of the grant of the Russian Science Foundation “Military Theme in the Architectural and Spatial Development of the Far East”. Based on the materials of field surveys and archival data, the authors have made the first attempt to comprehensively understand the historical process of architectural design of Vladivostok as a key Russian port on the Pacific coast. The surviving and lost buildings of the naval department, which were erected in the city and its environs at the turn of the 19th and 20th centuries, are considered. Their importance in the formation of the structure of the city panorama from the water area is noted.